Pharmacologic Treatment of Psychiatric Disorders and Time With Unsuppressed HIV Viral Load in a Clinical HIV Cohort. (1st November 2019) - Levy, Matthew E.; Monroe, Anne K.; Horberg, Michael A.; Benator, Debra A.; Molock, Sherry; Doshi, Rupali K.; Powers Happ, Lindsey; Castel, Amanda D.
Abstract : Objective: To evaluate associations of mood, anxiety, stress-/trauma-related, and psychotic disorders, both treated and untreated, with duration of unsuppressed HIV viral load (VL) among persons living with HIV (PLWH). Setting: The DC Cohort, an observational clinical cohort of PLWH followed from 2011 to 2018 at 14 sites in Washington, DC. Methods: Among PLWH ≥18 years old who received primary care at their HIV clinic, we determined in a time-updated manner whether participants had diagnoses and pharmacologic prescriptions for mood, anxiety, stress-/trauma-related, and/or psychotic disorders. Associations between psychiatric disorders/treatments and the proportion of subsequent days with VL ≥200 copies/mL were assessed using multivariable Poisson regression with generalized estimating equations. Results: Among 5904 participants (median age 51; 70% men; 82% Black), 45% had ≥1 psychiatric disorder, including 38% with mood disorders (50% treated), 18% with anxiety or stress-/trauma-related disorders (64% treated), and 4% with psychotic disorders (52% treated). Untreated major depressive disorder (adjusted rate ratio = 1.17; 95% confidence interval: 1.00 to 1.37), untreated other/unspecified depressive disorder (1.23; 1.01 to 1.49), untreated bipolar disorder (1.39; 1.15 to 1.69), and treated bipolar disorder (1.25; 1.02 to 1.53) (vs. no mood disorder) predicted more time with VL ≥200 copies/mL. Treated anxiety disorders (vs. no anxiety disorder) predicted less time (0.78; 0.62 to 0.99). Associations were weaker and nonsignificant for treated depressive disorders (vs. no mood disorder) and untreated anxiety disorders (vs. no anxiety disorder). Conclusions: PLWH with depressive and bipolar disorders, particularly when untreated, spent more time with unsuppressed VL than PLWH without a mood disorder. Treatment of mood disorders may be important for promoting sustained viral suppression. Abstract : Supplemental Digital Content is Available in the Text.